Photojournalism and Fake News. Genealogy and types of image manipulation: the case of the Agencia EFE - Caballo Méndez, Daniel; de Santiago Mateos, Miguel Ángel (Cuadernos de Documentación Multimedia, 2022)
The image as a visual support of the lie, in parallel to its recognized capacity to constitute itself as evidence of the reality, has had a great social repercussion since its inception. This article aims to analyze the phenomenon of “fake news” in photojournalism and, specifically, in photography in the field of the mass media; very especially in the context of news agencies. The objective of the work has two aspects: on the one hand, to establish as an approximation, the tools and resources – taking into account their evolution – that have been used to construct false images from the moment of the invention of photography and, secondly, point out a possible typology of image manipulation according to the characteristics established, a common denominator, of the most prominent situations in the reference studies in the research carried out in this field. Criteria that will be applied to the study of a specific case, that of image manipulation in the Spanish Agency EFE. Work that shows the scarce photographic manipulation (photographic “fake news”) in the studied institution, allows to conclude the existence of quality in the agency’s photojournalistic information and confirms the social repercussion of the subjects of manipulation analyzed.